1999
DOI: 10.1177/0148607199023003169
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Severe Copper Deficiency in a Patient With Crohn's Disease Receiving Parenteral Nutrition

Abstract: A 32-year-old man with active Crohn's disease and recurrent small bowel strictures underwent abdominal surgery and was subsequently given total parenteral nutrition (TPN). Severe cholestasis developed and copper was removed from the TPN. Although serum ceruloplasmin levels were within normal limits, 8 weeks after copper removal, he developed pancytopenia. Serum copper levels were severely depressed. Bone marrow biopsy was consistent with copper deficiency; cytoplasmic vacuolization of both myeloid and erythroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 19 publications
(10 reference statements)
2
48
0
Order By: Relevance
“…Copper deficiency has been observed in adult patients with inflammatory bowel disease (19,20), total parenteral nutrition (21,22), massive zinc ingestion (11) (6,(8)(9)(10)(11)(12)(13)(14)(15). Cytoplasmic vacuoles have also been found in patients with acute alcoholic intoxication (23), chloramphenicol toxicity (24), pancreatic dysfunction (25) and myeloproliferative syndromes (26).…”
Section: Discussionmentioning
confidence: 99%
“…Copper deficiency has been observed in adult patients with inflammatory bowel disease (19,20), total parenteral nutrition (21,22), massive zinc ingestion (11) (6,(8)(9)(10)(11)(12)(13)(14)(15). Cytoplasmic vacuoles have also been found in patients with acute alcoholic intoxication (23), chloramphenicol toxicity (24), pancreatic dysfunction (25) and myeloproliferative syndromes (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unclear why gender distribution of our patients showed more women than men (12 versus 1) (19)(20)(21)(22)(23), those with short bowel syndrome (24,25), and those with partial gastrectomy (12,26,27). In addition, sporadic case reports also suggested that inadequate diet alone or genetic disorders affecting proteins of copper metabolism could cause copper deficiency (28)(29)(30), including Menkes disease and occipital horn syndrome (10) …”
Section: Discussionmentioning
confidence: 75%
“…Several conditions causing thrombocytopenia in CD patients have been reported: 1) ITP (autoimmune platelet destruction); 2) druginduced thrombocytopenia, believed to induce autoimmunity or bone marrow suppression, reported following the use of anti-tumor necrosis factor (TNF)-alpha antibodies (i.e., infliximab) [6,7], 5-aminosalicylic acid [8], azathioprine [9], and low-molecular-weight heparin [10]; 3) the presence of thrombotic thrombocytopenic purpura (TTP) or hemolytic-uremic syndrome (HUS) in patients with CD [11][12][13]; 4) hematological malignancies [14] or portal hypertension (hypersplenism); and 5) deficiencies in minor elements, such as copper, during nutrition therapy for CD [15].…”
Section: Thrombocytopenia In CD Patientsmentioning
confidence: 99%